Impact of Distributed Generation Penetration on Distribution Network Technical Losses - João Tomé Saraiva (2019)
This work describes an analysis of the impact of distributed generation, focusing on the generation from renewable sources, in the technical losses of electrical energy distribution systems. To do so, the OPENDSS software was used to simulate the operation of two distribution feeders, considering: (a) different generation penetration levels; (b) generation with different power factors; (c) variations in the location of distributed sources in the distribution system. The results show that these factors can both interfere positively (decrease) or negatively (increase) in the distribution network technical losses levels, and therefore, there may be distortions in the recognized electrical losses by regulatory agencies, mainly due to the generation unpredictability of renewable sources. (c) 2019 IEEE.